IMPROVING DESCRIPTIVE WRITING THROUGH 'VK'S PROJECT' AUDIOVISUAL: A QUASI-EXPERIMENTAL STUDY - Selfiana Enjelia; Puput Zuli Ekorini (Universitas PGRI Mpu Sindok, 2025)
Many young people today frequently use more than one language, often mixing Indonesian with English in both oral and written communication. At MTs Al-Huda Gondang, a problem identified is students' lack of proficiency in constructing proper sentences, describing objects or events in detail, and understanding the correct structure of descriptive texts. This research aims to determine whether there is a significant difference in the descriptive text writing skills (on the topic of animals) of Grade VII students at MTs Al-Huda Gondang before and after the use of the